2011
DOI: 10.1590/s0006-87052011000300026
|View full text |Cite
|
Sign up to set email alerts
|

Influência do dano físico na fisiologia pós-colheita de folhas de taioba

Abstract: ResumoFolhas de taioba danificadas fisicamente tornam-se amarelas e escuras na região do dano. Assim, o objetivo deste trabalho foi avaliar o efeito do dano físico sobre o metabolismo pós-colheita de folhas de taioba. Para esse fim, avaliou-se o teor de clorofila e o acúmulo de compostos fenólicos solúveis em discos foliares de taioba que continham furos realizados com uma agulha em um dos lados da folha, simulando os danos sofridos no campo e transporte. O lado não danificado foi usado como tratamento control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Regarding the weight loss in tomatoes, Rab et al (2013) concluded that the change in fresh matter may have been caused by the loss of water through fruit transpiration and by resistance to moisture loss, which can decrease as the fruit progresses in maturation. Mendes et al (2011) evaluated vegetable products and concluded that, within few minutes after a physical damage, there was an increase in respiration, ethylene production and other biochemical reactions responsible for changes in color, texture and nutritional quality. For Beckles (2012), the maturity stage of tomato at harvest, as well as the pre-and post-harvest control, are essential factors to guarantee fruit quality.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the weight loss in tomatoes, Rab et al (2013) concluded that the change in fresh matter may have been caused by the loss of water through fruit transpiration and by resistance to moisture loss, which can decrease as the fruit progresses in maturation. Mendes et al (2011) evaluated vegetable products and concluded that, within few minutes after a physical damage, there was an increase in respiration, ethylene production and other biochemical reactions responsible for changes in color, texture and nutritional quality. For Beckles (2012), the maturity stage of tomato at harvest, as well as the pre-and post-harvest control, are essential factors to guarantee fruit quality.…”
Section: Resultsmentioning
confidence: 99%
“…The Hue angle refers to the value in degrees corresponding to the three-dimensional color diagram, in which: 0º-red, 90º-yellow, 180º-green and 270º-blue (Mendes et al, 2011;Chitarra & Chitarra, 2005). During the 15 days of storage, the Hº values for lamb's-ear leaves stored in the four packaging systems fluctuated, but at the end of the storage period the observed values were lower than those obtained on the first day (Figure 7).…”
Section: Hue (Hº)mentioning
confidence: 99%
“…These responses may occur after a few minutes to some hours after the injury at the damage site (local response) and at undamaged adjacent tissues (systemic response) (Leon et al, 2001). In tannia leaves, mechanical injury is visually detected by the yellowing, and later, some darkening restricted to the damaged region, not extending to the entire leaf (Mendes et al, 2011). The aim of this study was to evaluate the effect of mechanical injury on the physiological changes of tannia leaves and the eventual systemic responses from the site of injury into the adjacent undamaged areas.…”
Section: Introductionmentioning
confidence: 99%